The use of eHealth to promote physical activity in cancer survivors: a systematic review - Haberlin, Ciarán; O’Dwyer, Tom; Mockler, David; Moran, Jonathan; O’Donnell, Dearbhaile M.; Broderick, Julie (Supportive care in cancer, 2018)
Purpose Achieving adequate levels of physical activity (PA) and avoiding sedentary behaviour are particularly important in cancer survivors. eHealth, which includes, but is not limited to, the delivery of health information through Internet and mobile technologies, is an emerging concept in healthcare which may present opportunities to improve PA in cancer survivors. The aim of this systematic review was to explore the effects of eHealth in the promotion of PA among cancer survivors. Methods Suitable articles were searched using PubMed, CINAHL, EMBASE, PsychInfo, Web of Science and SCOPUS databases using a combination of keywords and medical subject headings. Articles were included if they described an eHealth intervention designed to improve PA in cancer survivors. Two reviewers screened studies for inclusion. Results In total, 1065 articles were considered. Ten studies met eligibility criteria. A variety of platforms designed to increase PA were described in these studies: web application (app) ( n = 5), web and mobile application ( n = 2), mobile app ( n = 1), website only ( n = 1), e-mail based ( n = 1). All studies measured PA using self-report outcome measures with the exception of one study which measured steps using a Fitbit. Meta-analysis was not performed because of variations in study design and interventions. All studies reported improvements in PA, with 8/10 studies reporting statistically significant changes. Conclusion The use of eHealth to promote PA in cancer survivors is a relatively new concept, which is supported by the recent emergent evidence described in this review. eHealth shows promise as a means of promoting and increasing daily PA, but further high-quality, longer term studies are needed to establish the feasibility and effectiveness of eHealth platforms aimed at that goal.